2021
DOI: 10.4102/sajhivmed.v22i1.1205
|View full text |Cite
|
Sign up to set email alerts
|

World AIDS Day 2020: Reflections on global and South African progress and continuing challenges

Abstract: Background: Reflecting on progress and challenges in meeting global human immunodeficiency virus (HIV) targets is often done ahead of World AIDS Day. This article reflects on progress and the continuing challenges in meeting targets in South Africa (SA).Objective: To review policy and implementation related progress and continuing challenges towards eliminating HIV as a public health threat by 2030.Method: Policy analysis and review of modeling data from Thembisa 4.3.Results: South Africa has made significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
0
21
1
Order By: Relevance
“…The findings of other studies also indicated that HIV testing services were reduced during the first season of the COVID-19 pandemic. 10 , 19–21 This could be because government-mandated lockdowns, which are intended to prevent the spread of COVID-19, have had a wide-range impact on health-care delivery. Furthermore, there was widespread public concern about contracting COVID-19 and being diagnosed with the condition, which resulted in a significant drop in VCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of other studies also indicated that HIV testing services were reduced during the first season of the COVID-19 pandemic. 10 , 19–21 This could be because government-mandated lockdowns, which are intended to prevent the spread of COVID-19, have had a wide-range impact on health-care delivery. Furthermore, there was widespread public concern about contracting COVID-19 and being diagnosed with the condition, which resulted in a significant drop in VCT.…”
Section: Discussionmentioning
confidence: 99%
“…HIV AIDS is one of the leading causes of death, accounting for around 690,000 deaths each year worldwide. 10 In 2020, an estimated 37.6 million people globally were infected with HIV, 1.3 million and 160,000 new adults and children was infected. 11 Around 16% of peoples living with HIV AIDS were unaware of their HIV status, 27% were unable to get antiretroviral therapy (ART), and 34% of those on ART were not virally suppressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where information was not available at the municipality level we defer, depending on data availability, to district or province. In 2020, a second round of quantitative data collection was conducted in relation to HIV so that newly published numbers from the 2019 Thembisa model could be included [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…With nearly eight million people in SA infected with HIV, the largest number globally, testing and initiating people infected with HIV on treatment are particularly important to reduce transmission. [16] The 22.3% decline in the number of people tested for HIV in 2020 means that fewer people living with HIV were initiated on treatment, resulting in SA not achieving the desired targets towards ending the AIDS epidemic. The decline in testing is similar for TB, with a 26% decrease in GeneXpert tests done in 2020.…”
Section: In Practicementioning
confidence: 99%